Coaching athletes with disabilities : challenges and recommendations for effective training / Nagoor Meera Abdullah - Abdullah, Nagoor Meera (Faculty of Sports Science and Recreation, 2010)
The article briefly discusses athletes with disabilities and how their condition can be matched with suitable activities to allow them to participate in physical activity and sports. The article also aims at assisting coaches who conducts training for people with disability to understand their condition first, and then devise programs that are appropriate for their condition. Furthermore, it highlights the barriers and conditions that affect athletes with disabilities participation in sports, especially those related to the health, safety, and medical considerations that coaches should understand and manage carefully. The article offers recommendations on how coaches should train athletes with disability.